2010
DOI: 10.2172/985846
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Pavements: A Critical Review of Existing Literature and Research

Abstract: This report provides a critical review of existing literature and modeling tools related to lifecycle assessment (LCA) applied to pavements. The review finds that pavement LCA is an expanding but still limited research topic in the literature, and that the existing body of work exhibits methodological deficiencies and incompatibilities that serve as barriers to the widespread utilization of LCA by pavement engineers and policy makers. This review identifies five key issues in the current body of work: inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 73 publications
2
31
0
5
Order By: Relevance
“…The process-based LCA method is usually used for construction projects since the methodology can disaggregate the projects into individual processes or activities independently (Santero et al, 2010). The life-cycle of pavement can be divided into different stages including raw material extraction, material processing and manufacturing, transportation, construction, maintenance, and end-of-life.…”
Section: Methodsmentioning
confidence: 99%
“…The process-based LCA method is usually used for construction projects since the methodology can disaggregate the projects into individual processes or activities independently (Santero et al, 2010). The life-cycle of pavement can be divided into different stages including raw material extraction, material processing and manufacturing, transportation, construction, maintenance, and end-of-life.…”
Section: Methodsmentioning
confidence: 99%
“…Such choices, which need to be made a priority, are quite a difficult task, as it is well known. The reason for this relies upon the different fates of the pavement that might be either landfilled, recycled, or sometimes used as the underlying structure for another pavement [15]. The section of the FU comprised two lanes and an emergency lane (on each carriageway) for a total width of asphalt pavement of 21 m. Specifically, the investigated product system accounts for the asphalt layers, i.e., surface course, binder course, and base layer.…”
Section: Environmental Burden Of the Asphalt Pavementmentioning
confidence: 99%
“…Several studies on the pavement are, in fact, present in the existing literature [13][14][15][16][17][18][19][20][21]. A critical review of fifteen studies, published by 2010, was provided by Santero et al [13][14][15]. Specifically, Santero considered the pavement life cycle as divided into five phases, that is: raw materials and production, construction, use, maintenance, and end of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is prominent from the literature that comparative road LCAs is the most common scope that compares different Table 1 Types of LCA (Baumann and Tillman, 2004 Santero et al (2010) that looked at different pavement LCA studies. It was concluded that the pavement LCA research studies have different depths, qualities and conclusions, and that it is very difficult to say which study data is reliable as data sources differ by large.…”
Section: Introductionmentioning
confidence: 99%
“…In his view, sustainability will play an important role in the projects decision support in future. Carlson (2011), in compliance with Santero et al (2010), concluded that it is impossible to directly compare the results of the road LCAs as the studies have different focus, functional units, system boundaries etc. Said et al (2012) provided an outline of the environmental impacts in pavement construction and maintenance in current road LCA literature and concluded that research in road LCAs is improving and expanding.…”
Section: Introductionmentioning
confidence: 99%